Meningkatkan Keamanan Sistem Informasi Puskesmas Terpadu dengan Metode Grey-Box Penetration Test Menggunakan Computer Assisted Audit Techniques - Nopan Pirsa; Sumijan Sumijan (SEULANGA SYSTEM PUBLISHER, 2020)
Information system security is something the owner must pay attention to in order to avoid cyber crime. Information systems that have security vulnerabilities can threaten an organization's critical infrastructure. Security vulnerabilities are any kind of vulnerability that allows attackers to enter into the system illegally and perform unwanted acts. Penetration tests on information systems need to be carried out to ensure its security. This study aims to improve the security of the integrated health center information system in Payakumbuh City so that data and information is guaranteed its security. The method used is the gray box penetration test using computer assisted audit techniques. The results of this study found 97 high vulnerability categories, 1 medium vulnerability category and 26 low vulnerability categories. The Payakumbuh City Information and Communication Office can take advantage of the penetration test results as a reference to improve the security of the Payakumbuh integrated health center information system.